Dynamic Analyses of Isolated Structures under Bi-Directional Excitations of Near-Field Ground Motions - Gokhan Ozdemir; Ugurhan Akyuz (Shock and Vibration)
Nonlinear response history analyses (NRHA) of a 3-story isolated reinforced concrete (RC) building are carried out under both uni- and bi-directional earthquake excitations of near-field records. NRHA are conducted for a wide range of yield strength (Q/W) of lead rubber bearings (LRB), and isolation period (T). Selected near-field records are used to investigate both the contribution of orthogonal components on maximum isolator displacements and accuracy of equivalent lateral force (ELF) procedure on estimation of maximum isolator displacements. Analyses results show that both the contribution of orthogonal components and accuracy of ELF procedure depend on the soil condition where isolation system is implemented.